Treatment with galectin-1 eye drops regulates mast cell degranulation and attenuates the severity of conjunctivitis - Mello-Bosnic, Claudia [UNESP]; Gimenes, Alexandre Dantas; Oliani, Sonia Maria [UNESP]; Gil, Cristiane Damas [UNESP] (Elsevier, 2018)
Galectin-1 (Gal-1) is a β-galactoside-binding protein with diverse biological activities in the pathogenesis of inflammation, however the mechanisms by which Gal-1 modulates cellular responses in allergic inflammatory processes have not been fully determined. In this study, we evaluated the therapeutic potential of Gal-1 eye drops in an experimental model of conjunctivitis. Wistar rats received a topical application of compound (C)48/80 (100 mg/ml) into right eyes and a drop of vehicle into the contralateral eye. Another group of rats received Gal-1 (0.3 or 3 μg/eye) or sodium cromoglycate (SCG; 40 mg/ml) in both eyes and, after 15 min, right eye was challenged with C48/80. Conjunctivitis-induced by C48/80 was characterized by severe eyelid oedema and tearing, but clinical signs were ameliorated by eye drop doses of both Gal-1 (0.3/3 μg) and SCG. As expected, an increased proportion of degranulated mast cells (62%, P < 0.01) and lower histamine levels were observed after 6 h of C48/80 challenge, compared to control (32%). This effect was abrogated by Gal-1 and SCG, which reduced mast cell degranulation (31–36%), eosinophil migration and eosinophil peroxidase levels in the eyes. Gal-1 (3 μg) and SCG treatments also decreased IL-4 levels, as well as activation of mitogen activated protein kinases compared to untreated C48/80 eyes. Our findings suggest that Gal-1 eye drops represent a new therapeutic strategy for ocular allergic inflammation.
Keywords: Compound 48/80; Eosinophil; Eye; Inflammation; Mitogen-activated protein kinases